Correlation Study Between Modification Types and Characteristics of Cassava Starch (Manihot utilissima) Using Pearson Correlation: Modified Cassava Starch - Windra, Ahmad; Ulyarti, Ulyarti; Sari, Dian Wulan (Jurnal Bio-Geo Material Dan Energi, 2022)
Starch modification is a process that can improve the properties of starch, so that it has good characteristics. Research on the modification of cassava starch using various modification methods resulted in changes in the characteristics of cassava starch. There are various results regarding the type of modification and their resulting characteristic of modified starch. This research aimed to obtain certain characteristics of cassava starch that have the potential to be modified using certain types of starch modification. The data used in this research is secondary data through searching scientific publications. The type of starch modification wasconsist of pre-gelatinization, cross-linking, acid hydrolysis, HMT, and fermentation while the starch characteristics were swelling power, solubility, water absorption, peak viscosity, and breakdown viscosity. The data collected was analyzed using Pearson's correlation. The correlation between the type of modification and swelling power and WAC is moderate, while the correlation between type of starch modification and solubility, peak viscosity, and breakdown viscosity are very weak. Swelling power and WAC are the characteristics of cassava starch that have the most potential to be modified with predictable results, while changes in solubility, peak viscosity, and breakdown viscosity in various types of modification are difficult to predict, because many other factors are involved besides the type of modification.